Evaluation of the Quality of Occupational Therapy Fieldwork Experiences - Drynan, Donna Patricia; Turnbull , Jennifer Ann; Currie, Leanne M. (International Journal of Practice-based Learning in Health and Social Care, 2018)
Practice education, or fieldwork as it is referred to in occupational therapy, is a fundamental feature of occupational therapy education, priming students to become competent entry-level practitioners. Factors reported as contributing to poor quality fieldwork experiences include: students not receiving enough feedback; lack of opportunity to develop skills; and not being made to feel welcome in the environment. These are significant contributors to the overall development of competence so it is important to understand the current context of fieldwork experiences being offered in relation to the notion of quality in those learning environments. The purpose of this study was to evaluate the quality of the fieldwork learning environment from the perspective of occupational therapists’ working in one region of Canada. A validated survey, the Quality of Occupational Therapy Fieldwork Experience (QOTFE) tool, was used to identify features of what might constitute quality fieldwork education, and to determine whether there was a difference in quality of fieldwork experience between practice settings or types of practice areas. However, there was minimal variability in scores based on practice setting and practice area variables. These findings indicate a consistent quality of fieldwork experience across practice settings and practice areas. This research presents a picture of the current quality of fieldwork experiences available to occupational therapy students. This may be a starting place for further investigation into the factors that contribute to the quality of practice education learning experiences